Host plants and insecticides shape the evolution of genetic and clonal diversity in a major aphid crop pest - Roy, Lise; Barrès, Benoit; Capderrey, Cécile; Mahéo, Frédérique; Micoud, Annie; Hullé, Maurice; Simon, Jean‐Christophe (Evolutionary applications, 2022)
Understanding the spatiotemporal dynamics of pesticide resistance at the landscape scale is essential to anticipate the evolution and spread of new resistance phenotypes. In crop mosaics, host plant specialization in pest populations is likely to dampen the spread of pesticide resistance between different crops even in mobile pests such as aphids. Here, we assessed the contribution of host‐based genetic differentiation to the dynamics of resistance alleles in Myzus persicae, a major aphid pest which displays several insecticide resistance mechanisms. We obtained a representative sample of aphids from a crop mosaic through a suction trap for 7 years and from various crops as a reference collection. We genotyped these aphids at 14 microsatellite markers and four insecticide‐resistant loci, analyzed the genetic structure, and assigned host‐based genetic groups from field‐collected aphids. Four well‐defined genetic clusters were found in aerial samples, three of which with strong association with host‐plants. The fourth group was exclusive to aerial samples and highly divergent from the others, suggesting mixture with a closely related taxon of M. persicae associated with unsampled plants. We found a sharp differentiation between individuals from peach and herbaceous plants. Individuals from herbaceous hosts were separated into two genetic clusters, one more strongly associated with tobacco. The 4‐loci resistance genotypes showed a strong association with the four genetic clusters, indicative of barriers to the spread of resistance. However, we found a small number of clones with resistant alleles on multiple host‐plant species, which may spread insecticide resistance between crops. The 7‐year survey revealed a rapid turn‐over of aphid genotypes as well as the emergence, frequency increase and persistence of clones with resistance to several families of insecticides. This study highlights the importance of considering landscape‐scale population structure to identify the risk of emergence and spread of insecticide resistance for a particular crop.